Fine specificity of anti-beta2glycoprotein I antibodies in systemic autoimmune diseases is mostly directed against domain 1 - P.L. Meroni; T. Avcin; V. Medeghini; A. Meini; A. Lojacono; M. Frassi; M. Nuzzo; Z. Shums; W.L. Binder; G.L. Norman; M. Motta; L. Andreoli; et al. (PAGEPress Publications, 2011)
Objective: Anti-b2 GPI are a formal laboratory criterion for the antiphospholipid syndrome (APS). They were demonstrated to be a risk factor for thrombosis and fetal losses but can also be detected in patients with systemic autoimmune disease (SAD), in healthy adults individuals and pre-school children. It has been suggested that different subpopulations of anti-b2GPI may carry different pathogenetic potential: autoantibodies against Domain1 seem to be associated with thrombosis; autoantibodies against Domain4/5 have been identifi ed in patients with non-thrombotic conditions. Methods: We studied 48 patients with SAD (32 systemic lupus erythematosus, 16 undifferentiated connettive tissue disease), 64 patients with APS, 57 one-year-old healthy children born to mother with SAD, 33 children with atopic dermatitis. All subjects were IgG anti-b2 GPI positive. The specifi city of anti-b2 GPI was investigated using ELISA research products containing recombinant b2 GPI D1 and D4/5 antigens. Cut-off values are calculated as 95th percentile on 100 NHD. IgG anti-b2 GPI were tested at a validated home-made ELISA routinely performed in our laboratory. No thrombotic events were recordered in patients with SAD and in both groups of children. Results: Patients with SAD and APS showed prevalent reactivity for D1 while children in both groups preferentially recognize D4/5. Conclusions: IgG anti-b2 GPI against D1 seem to cluster in patients with systemic autoimmune conditions. Their pathogenic potential in determine APS manifestations may be mitigated by adequate prophylaxis.